Social Engagement, Health, and Changes in Occupational Status: Analysis of the Korean Longitudinal Study of Ageing (KLoSA) - Min, Jin-young; Lee, Kyung-jong; Park, Jae-beom; Cho, Sung-il; Park, Shin-goo; Min, Kyoungbok (PLOS ONE, 2012)
Background We focused on whether changes in the occupational status of older male adults can be influenced by social engagement and health status measured at the baseline. Methods This study used a sample of the Korean Longitudinal Study of Aging (KLoSA), and the study population was restricted to 1.531 men who were aged 55 to 80 years at the 2006 baseline survey and participated in the second survey in 2008. Social engagement and health status, measured by the number of chronic diseases, grip strength, and depressive symptoms as well as covariates (age, marital status, educational level, and household income) were based on data from the 2006 baseline survey. Occupational engagement over the first and second survey was divided into four categories: ‘consistently employed’ (n = 892), ‘employed-unemployed’ (n = 152), ‘unemployed-employed’ (n = 138), and ‘consistently unemployed’ (n = 349). Results In the multinomial model, the ‘consistently employed’ and ‘unemployed-employed’ groups had significantly higher social engagement (1.19 and 1.32 times, respectively) than the referent. The number of chronic diseases was significantly associated with four occupational changes, and the ‘unemployed-employed’ had the fewest chronic conditions. Conclusion Our finding suggests that social engagement and health status are likely to affect opportunities to continue working or to start working for older male adults.